6-OHDA-Lesioned Adult Zebrafish as a Useful Parkinson’s Disease Model for Dopaminergic Neuroregeneration - Vijayanathan, Yuganthini; Lim, Fei Tieng; Lim, Siong Meng; Long, Chiau Ming; Tan, Maw Pin; Majeed, Abu Bakar Abdul; Ramasamy, Kalavathy (Springer Verlag, 2017)
Conventional mammalian models of neurodegeneration are often limited by futile axonogenesis with minimal functional recuperation of severed neurons. The emergence of zebrafish, a non-mammalian model with excellent neuroregenerative properties, may address these limitations. This study aimed to establish an adult zebrafish-based, neurotoxin-induced Parkinson’s disease (PD) model and subsequently validate the regenerative capability of dopaminergic neurons (DpN). The DpN of adult male zebrafish (Danio rerio) were lesioned by microinjecting 6-hydroxydopamine (6-OHDA) neurotoxin (6.25, 12.5, 18.75, 25, 37.5, 50 and 100 mg/kg) into the ventral diencephalon (Dn). This was facilitated by an optimised protocol that utilised 1,1′-dioctadecyl-3,3,3′,3′-tetramethyl-indocarbocyanineperchlorate (DiI) dye to precisely identify the injection site. Immunostaining was utilised to identify the number of tyrosine hydroxylase immunoreactive (TH-ir) DpN in brain regions of interest (i.e. olfactory bulb, telencephalon, preoptic area, posterior tuberculum and hypothalamus). Open tank video recordings were performed for locomotor studies. The Dn was accessed by setting the injection angle of the microinjection capillary to 60° and injection depth to 1200 μm (from the exposed brain surface). 6-OHDA (25 mg/kg) successfully ablated >85% of the Dn DpN (preoptic area, posterior tuberculum and hypothalamus) whilst maintaining a 100% survival. Locomotor analysis of 5-min recordings revealed that 6-OHDA-lesioned adult zebrafish were significantly (p < 0.0001) reduced in speed (cm/s) and distance travelled (cm). Lesioned zebrafish showed full recovery of Dn DpN 30 days post-lesion. This study had successfully developed a stable 6-OHDA-induced PD zebrafish model using a straightforward and reproducible approach. Thus, this developed teleost model poses exceptional potentials to study DpN regeneration.